Identification and characterization of a telomerase activity from Schizosaccharomyces pombe. - Lue, N F (1997)
A telomerase-like primer extension activity has been detected in chromatographic fractions derived from Schizosaccharomyces pombe extracts. This primer extension activity acts preferentially on dG-rich oligodeoxynucleotides, is sensitive to RNase A pretreatment and requires all four deoxynucleotides for optimal polymerization. The extension products are also truncated by the inclusion of any one of the four dideoxynucleotides, consistent with the presence of all four bases in the S.pombe telomeric repeats. The intensity distribution of the extension products and the dideoxynucleotide termination pattern suggest that nucleotide addition is template directed, and that telomere-like sequences are added to the primers. In particular, the sequence d(CGGTTA), a variant of the S.pombe telomeric repeat, can be added directly by the in vitro activity. Partially purified S.pombe telomerase sediments as a 35S particle, suggesting that it exists in vivo as part of a large multi-protein complex.